PENGARUH REBUSAN DAUN SALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Tamsuri, Anas; Nur, Afif Yunia (Akademi Keperawatan Pamenang, 2013)
Daily diet Indonesian people contains a lot of salt. Salt is one food that should be reduced if someone wants to avoid hypertension (high blood pressure). Hypertension is a common cause of stroke and heart attack. One treatment derived from herbs, which uses bay leaves. However, hypertensive patients in kauman / rinjani street RT20,21,22 RW 06Â do not know the majority of the benefits of bay leaves as lowering blood pressure. This study aimed to determine the effect of boiled of bay leaves to decrease in blood pressure in hypertensive patients.The research method used is a pre-experimental study design with one-group pretest-posttest design. Population of 27 respondents. Sample 12 people, with purposive sampling technique. I.e. people who have hypertension by age 33-55 years who are not currently undergoing treatment. Data collected using the observation sheet. Data analysis was done by calculating the mean manually.The result showed that the majority of respondents experienced a decrease of mean blood pressure pretest 144,16/91,66 to be135,41/85,83.From the description above it can be concluded that a decrease in blood pressure respondents boiled of bay leaves is given 2 times a day over a period of 7 days in a row. Means boiled of bay leaves can lower blood pressure in hypertensive patients. Suggested respondents continue to consume boiled leaves regularly.Â Keyword: Patient, Hypertension, boiled of bay leaves